Respuesta :

♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫

Just substitute 0 into everywhere you see x

f(0) = 2(0)^2 + 3(0)

f(0) = 0

Hope This Helps You!

Good Luck (:

Have A Great Day ^-^

↬ ʜᴀɴɴᴀʜ

Answer:

f(x-4) = 4, 5/2

f(0) = 0

Step-by-step explanation:

  f(x-4)=2(x-4)^2+3(x-4)

1. Square the (x-4) by itself

         2(x^2-8x+16)+3(x-4)

2. Distribute

         2x^2-16x+32+3x-12

3. Eliminate common factors

         2x^2-13x+20

4. Factor by grouping

         2x^2-8x-5x+20

         2x(x-4)-5(x-4)

5. Set equations to 0.

         x-4 = 0 x = 4

         2x-5 = 0 x = 5/2

2(0)^2+3(0) = 0